Understanding the Effects of Mixed Reality on Video Game Satisfaction, Enjoyment, and Performance. (June 2022) - Sinlapanuntakul, Weerachet; Derby, Jessyca L.; Chaparro, Barbara S.
Background: With the rising demand for the use and application of modern immersive technologies, recent studies have investigated the user experience of augmented reality (AR) and virtual reality (VR) for video game purposes. Despite AR's and VR's pervasiveness in the video game industry, research studies into the effects of mixed reality (MR) on video game experience are scarce. This study examined the impact of MR on video game satisfaction, enjoyment, and user performance of first-time users. Method: Participants played the same strategy video game across two platforms, an MR headset and a mobile device. A short version of the Game User Experience Satisfaction Scale (GUESS-18) and the Enjoyment scale (ENJOY) were used to measure satisfaction and enjoyment. Results: Results demonstrated that MR provided greater overall satisfaction, engrossment, creativity, and personal gratification. In addition, results revealed higher overall enjoyment, challenge/improvement, and engagement in the MR condition. Interestingly, participants performed better with the mobile version. No statistical differences were found between the conditions regarding the GUESS's usability, audio aesthetics, visual aesthetics, and the ENJOY's pleasure and competence. Conclusion: The study provides insight into how MR influences satisfaction and enjoyment for video games. Playing a video game in mixed reality has the potential to enhance the user experience of game players despite the possibility of simulator sickness and worse performance than traditional mobile environments. Features of the gameplay that enhanced as well as diminished video game experience are discussed.